Nonverbal communication and rituals in intercultural friendship development: A three-semester longitudinal study at a Chinese university - Anjum, Syed Waqas; Jinquan, Wang (Journal of International Students, 2026)
This longitudinal study explores the roles of nonverbal communication and cultural rituals in the development of intercultural friendships between Chinese and international students at a Chinese university. Spanning three semesters, the research investigates how students navigate cultural differences using nonverbal strategies such as silence, body language, proxemics, and shared rituals like gift-giving and communal meals. Findings show that nonverbal communication is essential for building trust, managing conflict, and regulating emotions. Silence is used for emotional reset and conflict avoidance, while shared rituals create a "third culture" that transcends cultural boundaries. The study extends symbolic interactionism by incorporating embodied nonverbal rituals and reinterpreting Face Negotiation Theory to demonstrate how these rituals function as facework. The concept of "third culture building" highlights how intercultural friendships evolve into shared cultural spaces. The results emphasize the importance of informal, student-driven practices and recommend that universities support these nonverbal strategies to foster inclusive environments.